Couette flows over a rough boundary and drag reduction - Jäger, Willi; Mikelić, Andro (Communications in mathematical physics, 2003)
We consider the Couette flow between two plates. The lower plate is fixed and has periodically placed riblets of the characteristic size ɛ on it.
Published online: 7 November 2002
Gesehen am 23.08.2018